Surface Characterization of New β Ti-25Ta-Zr-Nb Alloys Modified by Micro-Arc Oxidation - Kuroda, Pedro Akira Bazaglia; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (MDPI, 2023)
The technique of surface modification using electrolytic oxidation, called micro-arc oxidation (MAO), has been used in altering the surface properties of titanium alloys for biomedical purposes, enhancing their characteristics as an implant (biocompatibility, corrosion, and wear resistance). The layer formed by the micro-arc oxidation process induces the formation of ceramic oxides, which can improve the corrosion resistance of titanium alloys from the elements in the substrate, enabling the incorporation of bioactive components such as calcium, phosphorus, and magnesium. This study aims to modify the surfaces of Ti-25Ta-10Zr-15Nb (TTZN1) and Ti-25Ta-20Zr-30Nb (TTZN2) alloys via micro-arc oxidation incorporating Ca, P, and Mg elements. The chemical composition results indicated that the MAO treatment was effective in incorporating the elements Ca (9.5 ± 0.4 %atm), P (5.7 ± 0.1 %atm), and Mg (1.1 ± 0.1 %atm), as well as the oxidized layer formed by micropores that increases the surface roughness (1160 nm for the MAO layer of TTZN1, 585 nm for the substrate of TTZN1, 1428 nm for the MAO layer of TTZN2, and 661 nm for the substrate of TTZN2). Regarding the phases formed, the films are amorphous, with low crystallinity (4 and 25% for TTZN2 and TTZN1, respectively). Small amounts of anatase, zirconia, and calcium carbonate were detected in the Ti-25Ta-10Zr-15Nb alloy.
Keywords: micro-arc oxidation; surface modifications; titanium alloys